Extração e caracterização de compostos fenólicos de folhas de amoreira preta (Morus nigra L.) e encapsulamento em esferas de alginato - Schafranski, Kathlyn (2019)
Black mulberry (Morus nigra L.) is a plant of Asian origin, acclimatized in Brazil, and its leaves are used as infusions, due to beneficial health properties. Its antioxidant and anticancer action has been demonstrated and can be attributed to the presence of phenolic compounds in the plant. However, this class of compounds has low stability and one of the alternatives of conservation of the bioactivity of these compounds can be the encapsulation. The objective of this work is the extraction of phenolic compounds from leaves of black mulberry for later encapsulation in spheres of calcium alginate. Initially, aqueous extracts of Morus nigra leaves were prepared through an experimental design to determine the best conditions of drying and infusion temperatures and extraction time regarding their total phenolic content (CFT). Concentrations of CFT, flavonoids, flavonols, ortho-diphenols, antioxidant activity against DPPH radical and total extractive capacity were determined. Identification and quantification of phenolic compounds by high performance liquid chromatography coupled to mass spectrometry (LC-ESI-MS / MS). Concentrations of minerals were determined. The antimicrobial activity of the extracts was also performed. The extracts were encapsulated in calcium alginate beads and evaluated in terms of CFT, encapsulation efficiency tests, release of the active principle in water, storage stability and ball characterization. Among the evaluated conditions the most efficient extractions occurred in leaves that were exposed to lower drying temperatures and higher infusion temperatures. The extracts showed appreciable concentrations of phenolic classes and antioxidant activity. Analysis by LC-ESI-MS / MS allowed to identify phenolic substance not yet reported in the literature to date. In addition 10 mineral elements were determined in significant concentrations, among them potassium, iron and manganese. The encapsulation efficiency of CFT for dry and wet spheres was 95.1 ± 1.4 and 81.7 ± 0.8% respectively. SEM images for dry spheres showed that the extract and drying affected the morphology of the spheres. FTIR spectra of beads loaded with extract showed compatibility between the phenolic compounds and the alginate matrix. Along the 81 days of storage, the dried spheres kept at 4 °C showed stability in CFT up to 36 days, however small changes in CFT were observed until the end of the period. For moist spheres stored at 4 °C, CFT remained stable for the first four weeks. Thus, the encapsulation of black mulberry extracts in alginate beads is a promising technique to promote protective action of phenolic compounds.